Gusjigang and Da’wa Sunan Kudus in Preserving Spiritual and Islamic Economic Value in Recession Year - Muhajarah, Kurnia; Cahyaningrum, Belia; Tanjung, Rahmy Fuady; Kamaliah, Naily; Norannabiela, Norannabiela (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2022)
The background of this research is based on the advancement of the education and economic sectors in the Kudus Regency after the arrival of Sunan Kudus with the teachings of Islam and its Gusjigang philosophy. The purpose of this study was to determine the spiritual and economic values in the Gusjigang philosophy and its influence on the trading community in Kudus. This type of research is qualitative with a phenomenological approach. Data collection techniques were taken through observation, interviews, and documentation. The source of the data for this research is the trader community in Kota District, Kudus Regency. The analytical technique used is a phenomenological approach that takes a person's experience through descriptions of people who are research participants. The results of the study found that the spiritual and economic values ​​in the Gusjigang philosophy in the trader community in Kota District were an effort to achieve prosperity in religious and daily life seen from the activities of traders who applied attitudes in accordance with the values ​​of Gus, Ji and Gang. The influence of this philosophy can be seen in the number of educational institutions, Islamic boarding schools, and the advancement of the trade and industrial sectors.